Жіночі чернечі спільноти Галичини в контексті легалізації УГКЦ наприкінці 80-х рр. ХХ ст. - Маслій, Ольга; Masliy, Olga (My University, 2015)
У статті розглянуто участь жіночих чернечих спільнот Галичини в процесі легалізації УГКЦ наприкінці 80-х рр. ХХ ст. Висвітлено роль чернецтва в маніфестаціях, зверненнях до державної влади та ін., що мали за мету тиск на партійно-радянське керівництво для відновлення УГКЦ.. Monastic communities continued their activities during the years of persecution of Church, from 1946 to legalization in 1989. The nuns were active participants in the underground organization of persecuted church. In 1989 to UGCC belonged ten female religious communities, which had more than 300 nuns, who joined the community after the dissolution of the monasteries by the Soviet authorities in 1946. Consecrated persons represented also a constituent institution of banned church - monasticism, which suffered harassment, imprisonment and persecution from the government.
Women Monastic Communities in Galicia in the Context of the Legalization of UGCC end of 80-ies in XX Century
Keywords: державна влада; легалізація; Українська греко-католицька церква; чернецтво; state government; legalization; Ukrainian Greek Catholic Church; monasticism